2016
DOI: 10.1007/s11244-016-0684-x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation: From a Still Immature Technology to the Roots of Catalysis Science

Abstract: The design of heterogeneous selective oxidation catalysts based upon complex metal oxides is governed at present by a set of empirical rules known as “pillars of oxidation catalysis”. They serve as practical guidelines for catalyst development and guide the reasoning about the catalyst role in the process. These rules are, however, not based upon atomistic concepts and thus preclude their immediate application in for example computer-aided search strategies. The present work extends the ideas of the pillar rul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 147 publications
(164 reference statements)
0
53
0
Order By: Relevance
“…[44][45][46] It has also been demonstrated that oxidative dehydrogenation of ethanol could be used as a model reaction to investigate the redox properties of V 2 O 5 /TiO 2 catalysts. 47 Inspired by these studies, we also applied ethanol oxidation as a model reaction to investigate these properties of the catalysts used for LA conversion.…”
Section: Catalytic Mechanismmentioning
confidence: 99%
“…[44][45][46] It has also been demonstrated that oxidative dehydrogenation of ethanol could be used as a model reaction to investigate the redox properties of V 2 O 5 /TiO 2 catalysts. 47 Inspired by these studies, we also applied ethanol oxidation as a model reaction to investigate these properties of the catalysts used for LA conversion.…”
Section: Catalytic Mechanismmentioning
confidence: 99%
“…Achieving this objective would pave a new way to realize the environmentally friendly and sustainable production of value‐added chemicals, in which the use of catalysis and the reduction of toxic reagents, stoichiometric amounts of promoters, waste, energy, and number of operational steps are important factors ,. In the current petroleum‐based production system, chemical production processes are mainly based on the catalytic oxidation of raw materials such as hydrocarbons, which reside in low oxidation states . In order to diminish the use of fossil petroleum resources and carbon dioxide (CO 2 ) emissions, alternative synthetic routes starting from renewable carbon resources are required, even though renewable carbon resources such as CO 2 and biomass derivatives such as carboxylic acids, esters, and amides exhibit high oxidation states .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Mars-van-Krevelen mechanism prevalent in these oxidation reactions, the role of lattice oxygen must be analyzed further to quantify their transport between the bulk and surface regions, as well as understand their role in selectivity [81]. The site isolation concept for oxidation catalysts is based on the idea that this reactive oxygen must be readily available while the rest of the structure acts as a control system for the electronic and physical properties of the catalysts [82].…”
Section: Discussionmentioning
confidence: 99%
“…The low oxygen reaction order indicates that the generation of activated oxygen is not involved in the kinetically-difficult step [81]. However, the rates with respect to different intermediate steps, C-H activation, C-C breaking, C-O formation, etc., are not yet systemically studied or known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation